VARIATIONS IN LEUKOCYTE COUNTS OF TUBERCULOSIS PATIENTS DURING THE TREATMENT PERIOD - mfh, aini aini (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2024)
Background: Tuberculosis is one of the deadliest infectious diseases in the world. The disease is caused by Mycobacterium tuberculosis bacteria that spread in the air through the saliva of the patient. Infection from these bacteriacauses an increase in leukocytes in the blood as a form of body resistance in the process of phagocytosis. Administrationof anti-tuberculosis drugs during the first-line phase can kill bacteria and relieve symptoms arising from infection becausethese drugs have an effect on the work of the spinal cord in producing new blood cells. Research Objective: This study aims to determine the variation of leukocyte count of tuberculosis patients who are undergoing the first-line phase of treatment as an indication of cure rate. Research Methods: The research method used was analytic cross sectional, whichwas then analyzed by performing normality and homogeneity tests, then continued with the one way anova test. Results: The results of this study showed the average leukocyte value in the first month of treatment was 5,026 cells/mm3 blood, month two 9,415 cells/mm3 blood, month three 6,140 cells/mm3 , month four 6,566 cells/mm3 , month five 6,054 cells/mm3, and month six 6,667 cells/mm3 . With an average value of all 6,776 cells/mm3 . Conclusion: From these results, it can be concluded that there is a significant difference in the variation of leukocyte counts between the six treatment duration groups with an overall mean value of 6,776 cells/mm3 blood... The significant difference in leukocyte count variation between the six treatment duration groups indicates that leukocytes can be used as a benchmark to determine indications of the recovery rate of tuberculosis patients who are undergoing the first line of treatment.